Promises made, promises broken : a model of IMF program implementation - Joseph P. Joyce (Wellesley College, Department of Economics, 2003)
This paper presents a model of the implementation of IMF programs, which is empirically tested with data from the period 1975-99. The IMF and the borrowing country are shown to have asymmetric evaluations of a program?s discounted benefits, due to differences in the measurement of the benefits, the relevant time frame and appropriate discount rate. The model also distinguishes between a government that seeks to maximize national welfare and an autocracy that seeks only to benefit the ruling group. The results of the empirical analysis demonstrate that program implementation is affected by a country?s trade openness, the ideological cohesion of the government, the duration of the political regime, and the degree of political openness.
Keywords: F33; O19; 330; IMF programs; conditionality; Anpassungsprogramm des IWF; Entwicklungsländer